Respuesta :

Answer:

B. (5/6)^2

Step-by-step explanation:

A. 2^3

= 2 × 2 × 2

= 8

The base is 2

Therefore, the expression is greater than the base

B. (5/6)^2

= 5/6 × 5/6

= 5*5 / 6*6

= 25/36

Base = 5/6 = 0.833

Expression =25/36 = 0.694

Therefore, the expression is less than the base

C. 3^1

= 3

The base is 3

Therefore, the expression is equal to the base

D. 4^4

= 4 * 4 * 4 * 4

= 256

The base is 4

Therefore, the expression is greater than the base

The correct answer is B. (5/6)^2

ACCESS MORE